2017
DOI: 10.1007/s11606-017-3982-5
|View full text |Cite
|
Sign up to set email alerts
|

Physician and Patient Views on Public Physician Rating Websites: A Cross-Sectional Study

Abstract: Physicians and patients have different views on whether independent or health system physician rating websites are the more reliable source of information. Their views on whether such data should be shared on public websites are also discordant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 12 publications
1
87
1
Order By: Relevance
“…Consistent with our findings, prior research has shown that individuals are becoming more and more suspicious of the ratings posted on healthcare websites. For instance, Holliday et al [12] found that 57% of the patient respondents in their study expressed a high level of trust and perceived accuracy of numerical ratings and narrative comments published on independent PRWs; whereas, only 43% of them had positive attitudes toward similar information that were published on healthcare organizations' websites. Interestingly, most of the physician respondents in that study believed that the accuracy and trustworthiness of rating information published on the providers' websites were higher than those provided by independent PRWs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Consistent with our findings, prior research has shown that individuals are becoming more and more suspicious of the ratings posted on healthcare websites. For instance, Holliday et al [12] found that 57% of the patient respondents in their study expressed a high level of trust and perceived accuracy of numerical ratings and narrative comments published on independent PRWs; whereas, only 43% of them had positive attitudes toward similar information that were published on healthcare organizations' websites. Interestingly, most of the physician respondents in that study believed that the accuracy and trustworthiness of rating information published on the providers' websites were higher than those provided by independent PRWs.…”
Section: Discussionmentioning
confidence: 85%
“…Prior studies in the context of health social media have examined the characteristics of PRWs [17,18] as well as the characteristics and views of users versus non-users of those websites [12,26]. For example, Lagu et al [18] analyzed more than 8,000 reviews on 28 PRWs and found that the average numbers of ratings and comments per physician were significantly different across those websites.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of JGIM, Halliday et al 4 report the results of a survey assessing physician and patient perceptions of independent physician rating websites and about publicly publishing health system-based patient experience surveys. The study provides the opportunity to compare patient and physician responses regarding making physician ratings publicly available and to compare views on websites with different ownership and potentially different standards of data collection.…”
Section: How Do Patients and Physicians Perceive The Ratings And Commmentioning
confidence: 99%
“…The response to the rise in the popularity of physician rating websites is evolving, with early recommendations urging physicians to be patient-centered, recognize the value of understanding the patient's perspective, and use the ratings as feedback about areas in need of improvement. 5 An impetus for the survey designed by Halliday et al 4 was the efforts by health systems to increase the accessibility of their internal patient experience surveys by making ratings derived from these surveys publicly available. Thus, these findings should be considered in the context of recent moves by some health systems to post survey results on their websites.…”
Section: Physicians Should Consider How To Embrace Online Reviewsmentioning
confidence: 99%